2014
DOI: 10.1111/cas.12556
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of RTKs expression identified HER3 as a prognostic indicator of gastric cancer

Abstract: Standard treatment in Japan for the 13th Japanese Gastric Cancer Association stage II/III advanced gastric cancer is postoperative adjuvant S-1 administration after curative surgery. High expression of receptor type tyrosine kinases (RTKs) has repeatedly represented poor prognosis for cancers. However it has not been demonstrated whether RTKs have prognostic relevance for stage II/III gastric cancer with standard treatment. Tumor tissues were obtained from 167 stage II/III advanced gastric cancer patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
1
12
1
Order By: Relevance
“…Of the 172 patients, informed consent to use specimens was obtained from 167 patients, for whom the median follow up term was 75 months (inter quartile range, 61-90 months). These patients were identical to the patients whom we had analyzed previously (22).…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…Of the 172 patients, informed consent to use specimens was obtained from 167 patients, for whom the median follow up term was 75 months (inter quartile range, 61-90 months). These patients were identical to the patients whom we had analyzed previously (22).…”
Section: Methodssupporting
confidence: 60%
“…We have previously analyzed various RTK expressions and reported that HER3 and EGFR were significant and marginally significant independent prognostic factors, respectively, in patients with stage II/III gastric cancer who underwent curative gastrectomy followed by adjuvant chemotherapy with S-1 (22). However, we have not included this critical RTK of FGFR2 in the study.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, previous studies reported a poor survival in GC with a high ERBB3 expression [30,31] . Since the cytoplasmic ERBB3 expression was regarded as a positive expression in those reports, a consensus guideline for ERBB3 expression is needed to resolve the contradictory results [32] .…”
Section: Discussioncontrasting
confidence: 61%
“…HER2 immunostaining (defined as +3 immunostaining) is the well-established molecular target in far advanced gastric cancer using trastuzumab[20], but HER2-positive cases are infrequently found in recurrent gastric cancer[12]. Even in high-risk advanced gastric cancer, HER2-positive cases were infrequently seen (Table 4), while HER3-positive cases were frequently found.…”
Section: Discussionmentioning
confidence: 99%